2018
DOI: 10.1002/14651858.cd013030
|View full text |Cite
|
Sign up to set email alerts
|

Digital interventions to improve adherence to maintenance medication in asthma

Abstract: Farmer 1999 Farmer KC. Methods for measuring and monitoring medication regimen adherence in clinical trials and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 59 publications
0
35
0
2
Order By: Relevance
“…Digital tools may support treatment adherence; however, there are limitations. For example, Electronic Monitoring devices (EMDs) can be used with inhalation devices and pill bottles to record doses dispensed, 5 but they cannot ensure correct inhalation technique or actual medication‐taking 3,6 . Several Novel EMDs, for example Hailie‐Smart‐Inhaler, are in development to assess both inhalation and actuation 7 …”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations
“…Digital tools may support treatment adherence; however, there are limitations. For example, Electronic Monitoring devices (EMDs) can be used with inhalation devices and pill bottles to record doses dispensed, 5 but they cannot ensure correct inhalation technique or actual medication‐taking 3,6 . Several Novel EMDs, for example Hailie‐Smart‐Inhaler, are in development to assess both inhalation and actuation 7 …”
Section: Commentarymentioning
confidence: 99%
“…EMDs were found to be the most effective digital intervention for improving adherence, followed by SMS messages (Figure 1). The website‐based interventions had no significant effect on adherence but interestingly noted to be the most effective in improving asthma control as assessed by standardised patient questionnaires, followed by SMS messages 5 . A broad range of digital interventions have been considered here, and this sub‐group analysis is important when deciding what to recommend in clinic.…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations
“…Many interventions have been designed to support adherent behaviour across a range of conditions and treatments with varying degrees of efficacy (e.g. Chan et al, 2018;Conn & Ruppar, 2017;Horne, 1998;Kripalani et al, 2007;MacDonald et al, 2016;Nieuwlaat et al, 2014;Pearce et al, 2022). One systematic review found that only 16 out of 37 trials reported an improvement in adherence across chronic conditions, and suggested that interventions involving monitoring and feedback, or reducing dosing demands were most likely to be effective (Kripalani et al, 2007).…”
Section: Interventions To Support Adherencementioning
confidence: 99%